Development of an autonomous vision sensor-actuator-based circumferential seam path tracker welding machine/device for LPG cylinders - Kartik Kumar; Ruby Mishra; Surjeet Singh; Ashwani Kumar; Anish Pandey (Memories - Materials, Devices, Circuits and Systems, 2022)
This paper presents an autonomous vision sensor-actuator-based circumferential seam path tracker welding machine/device for LPG (Liquefied Petroleum Gas) cylinders. The machine or device is designed to avoid various hazardous health issues that are found in the workers due to unfavorable working conditions during the welding process because of high temperature, dangerous fumes, and a large amount of luminous flux in the workstation. This machine involves a pneumatic holder to hold the cylindrical workpiece inside a metallic body frame. When the cylindrical workpiece rotates in a pneumatic holder, some amount of deflection arises due to the improper arrangement of fixtures and cylinders. It is not easy to overcome this deflection in fixtures, and due to this, the welding process is not done correctly. The undercut and overcut errors can also be found due to the improper shape of fixtures and cylinders. Therefore, the box setup is designed to cope with this problem, and the box contains an RGB (Red Green Blue) camera, LED (Light Emitting Diode), and an ultrasonic sensor. The box is installed in front of the welding torch to capture the image of the seam path of the workpiece. Firstly, the image is created with the help of a LED fitted inside the box. The LED creates the shadow of the joggle joint of the cylindrical workpiece. The camera captures that shadow. After capturing the image of shadow, the centroid of the seam path (represented by shadow) of the cylindrical workpiece is traced. It is sent to the Raspberry Pi microcontroller, and the data of the image is stored in the memory of the microcontroller for further processing. According to the position of the centroid coordinate, the microcontroller sends the control commands to the microstep driver of the stepper motor to follow this centroid coordinate. By this, the torch is controlled, and the welding process is done autonomously. The experimental setup is made, and the autonomous welding process is performed in many cylinders. Moreover, after performing autonomous welding process in the cylinder, the high-pressure bursting test (which is basically done by cylinder manufacturer industries) is performed to verify the effectiveness and efficiency of the welding joints. In the bursting test result, it is found that the cylinder is burst in a longitudinal direction, which verifies the effectiveness and efficiency of the obtained circumferential joggle joints